DEVELOPING SELF-ASSIGNMENT SKILLS: THE KEY TO QUALITY EDUCATION - Azizbek Botirov (American Journals, 2023)
The role of independent work of students in modern education is important and integral. The article examines the concept of independent work, its importance in the educational process, as well as its impact on the professional growth and development of students. The literature review highlights the need to manage students' independent work, including planning, organizing, monitoring and analysing results. Methodology and empirical analysis reveal the psychological conditions that contribute to the successful independent work of students. In general, the article pays attention to the importance of independent work of students and its impact on their professional development.
Keywords: Independent work, extracurricular time, vocational education, state standard, selfstudy, new learning technologies.